Emergence of sovereign wealth funds - Carpantier, J; Vermeulen, W (University of Oxford, 2014)
This paper tests the theoretically founded hypothesis that the surge of SWF establishments is determined by three main factors: 1) the existence of natural resources profits, 2) the government structure and 3) the ability to invest usefully in the domestic economy. We test this hypothesis on a sample of 20 countries that established an SWF in the period 1998-2008 by comparing them to the roughly 100 countries that did not set up a fund in the same period. We find evidence for all three factors. The results suggest that SWFs tend to be established in countries that run an autocratic regime and have difficulties finding suitable opportunities for domestic investments. We do not find the net foreign asset position of a country to be similarly related to the explanatory variables, indicating that the establishment of an SWF is distinct from a national accounting result. We argue that our results indicate that it is relevant to study how an SWF interacts with the domestic economy and government policy.